Nucleofection: A New Method for Cutaneous Gene Transfer?. (20th November 2006) - Jacobsen, Frank; Mertens-Rill, Janine; Beller, Juergen; Hirsch, Tobias; Daigeler, Adrien; Langer, Stefan; Lehnhardt, Marcus; Steinau, Hans-Ulrich; Steinstraesser, Lars
Abstract : Background . Transfection efficacy after nonviral gene transfer in primary epithelial cells is limited. The aim of this study was to compare transfection efficacy of the recently available method of nucleofection with the established transfection reagent FuGENE6. Methods . Primary human keratinocytes (HKC), primary human fibroblasts (HFB), and a human keratinocyte cell line (HaCaT) were transfected with reporter gene construct by FuGENE6 or Amaxa Nucleofector device. At corresponding time points, β -galactosidase expression, cell proliferation (MTT-Test), transduction efficiency (X-gal staining), cell morphology, and cytotoxicity (CASY) were determined. Results . Transgene expression after nucleofection was significantly higher in HKC and HFB and detected earlier (3 h vs. 24 h) than in FuGENE6. After lipofection80 % –90 % of the cells remained proliferative without any influence on cell morphology. In contrast, nucleofection led to a decrease in keratinocyte cell size, with only20 % –42 % proliferative cells. Conclusion . Related to the method-dependent increase of cytotoxicity, transgene expression after nucleofection was earlier and higher than after lipofection.